CROWDFUNDING AND GROWTH OF SMALL AND MEDIUM ENTERPRISES IN NIGERIA - Majeed Ajibola Ibrahim; Adedeji Daniel Gbadebo; Joseph Olorunfemi Akande (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Crowdfunding has emerged as a vital alternative financing mechanism. The increased economic activity of small and medium enterprises (SMEs) due to crowdfunding has a ripple effect, stimulating broader growth for the sector. This research underscores the transformative potential of crowdfunding by examining how the increase in financial performance, innovation capabilities, and job creations of SMEs due to crowdfunding has impacted the growth of selected SMEs. The study uses survey design to gather data involving 50 owners of registered SMEs in Ibadan, Nigeria. The information gathered from the questionnaires were coded and used to complete a regression analysis to retain the study aims. The evidence identifies that only financial performance and improved innovation from the SMEs due to crowdfunding have positive and significant impacts on their growth. We suggest recommendations that would enhance the attractiveness of crowdfunding, such as government implementing policies that support crowdfunding as well as the creation of awareness and education for crowdfunding participants.